Does breastfeeding duration decrease child obesity? An instrumental variables analysis. Issue 4 (10th May 2016) - Modrek, S.; Basu, S.; Harding, M.; White, J. S.; Bartick, M.C.; Rodriguez, E.; Rosenberg, K. D.
Summary: Background: Many studies have documented that breastfeeding is associated with a significant reduction in child obesity risk. However, a persistent problem in this literature is that unobservable confounders may drive the correlations between breastfeeding behaviors and child weight outcomes. Objective: This study examines the effect of breastfeeding practices on child weight outcomes at age 2. Methods: This study relied on population‐based data for all births in Oregon in 2009 followed for two years. We used instrumental variables methods to exploit variations in breastfeeding by mothers immediately after delivery and the degree to which hospitals encouraged mothers to breastfeed in order to isolate the effect of breastfeeding practices on child weight outcomes. Results: We found that for every extra week that the child was breastfed, the likelihood of the child being obese at age 2 declined by 0.82% [95% CI −1.8% to 0.1%]. Likewise, for every extra week that the child was exclusively breastfed, the likelihood of being obese declined by 0.66% [95% CI −1.4 to 0.06%]. While the magnitudes of effects were modest and marginally significant, the results were robust in a variety of specifications. Conclusion: The results suggest that hospital practices that support breastfeeding may influence childhood weight outcomes.